Vocational High School Teachers’ Pedagogical Competence in Teaching English - Heri Hidayatullah; Siti Syafi’atul Qomariyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
Pedagogical competency is one of several competencies that teachers have to have merely for being a professional teacher. Referring to the process of recruitment held by governments and the reality of the teaching and learning process in the context of formal school, this current study tried to find out how the teachers’ pedagogical competence, especially in vocational high school. A descriptive qualitative research design was applied in order to deeply dig and analyzed the data needed. The subjects of the research were two teachers along with their own students. Interview and questionnaire were distributed to collect data and then analyzed using triangulation. The findings showed that the teachers understand and know well about their students’ learning styles which in turn to design and implement their teaching and learning via making conversation with the students and doing a pretest. However, most of the students’ responses were in contrast with the teachers’ responses. It could be concluded that the teachers’ pedagogical competence was categorized into low level due to not all students in their classes being invited to do conversation.